2020
DOI: 10.1515/nanoph-2020-0136
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-responsive multicolor emission of single NaGdF4:Yb/Ce/Ho upconversion nanocrystals for anticounterfeiting application

Abstract: AbstractThis study presents a novel and high-level anticounterfeiting strategy based on Ce/Yb/Ho triply-doped NaGdF4 nanocrystals with temperature-responsive multicolor emission. A critical factor leading to the multicolor emission is confirmed by comparing the luminescence thermal behaviors of nanocrystals in various atmospheres. Through analyzing the temperature-dependent lifetimes of Yb3+ ions in air, we demonstrate that thermally-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…demonstrates the potential of our Ho 3+ -based thermometer, reflected by the strong color shift with increasing temperature going from red through white to green. [23][24][25][26] Specifically, we prepared microcrystalline fluoride compounds doped with different concentrations of Ho 3+ , i.e., β-NaY 0.75−x Gd 0.25 Ho x F 4 (Figure 1b). [27] Excitation of these samples with 450 nm light results in a blue, a green, and a red emission band, which are due to the 5 F 3 → 5 I 8 , 5 F 4 , 5 S 2 → 5 I 8 , and 5 F 5 → 5 I 8 + 5 F 3 → 5 I 7 radiative transitions respectively.…”
Section: Figure 1amentioning
confidence: 99%
“…demonstrates the potential of our Ho 3+ -based thermometer, reflected by the strong color shift with increasing temperature going from red through white to green. [23][24][25][26] Specifically, we prepared microcrystalline fluoride compounds doped with different concentrations of Ho 3+ , i.e., β-NaY 0.75−x Gd 0.25 Ho x F 4 (Figure 1b). [27] Excitation of these samples with 450 nm light results in a blue, a green, and a red emission band, which are due to the 5 F 3 → 5 I 8 , 5 F 4 , 5 S 2 → 5 I 8 , and 5 F 5 → 5 I 8 + 5 F 3 → 5 I 7 radiative transitions respectively.…”
Section: Figure 1amentioning
confidence: 99%
“…[99] The heat-induced UCL enhancement assisted by water molecules has been confirmed by previous studies, showing that the UCL enhancement could be more than a magnitude in some cases. [100][101][102][103] Apart from surface water molecules, Zhou et al reported the discovery of a surface "dark layer," which was formed via the surface vibrations of the YbO coordination bonding and could be affected by local temperature. [96] By taking advantage of the discovery, they then resort to the thermal method to manipulate the surface condition of Tm 3+ -doped NaYF 4 UCNPs, which exhibited more than 2000 times enhancement of 450 nm emission intensity by elevating the local temperature from room temperature to 453K (Figure 9d).…”
Section: Regulating Upconversion By Heatmentioning
confidence: 99%
“…[ 99 ] The heat‐induced UCL enhancement assisted by water molecules has been confirmed by previous studies, showing that the UCL enhancement could be more than a magnitude in some cases. [ 100–103 ] Apart from surface water molecules, Zhou et al. reported the discovery of a surface “dark layer,” which was formed via the surface vibrations of the YbO coordination bonding and could be affected by local temperature.…”
Section: Remote Regulation Of Upconversionmentioning
confidence: 99%
“…6,7 Lanthanide-doped upconversion nanoparticles (UCNPs) possess abundant discrete energy levels with diverse thermaldependent electronic transitions, 8−11 which have attracted tremendous attention in the temperature sensor during the past decade. 6,12,13 Typically, the UCNPs based temperature thermometry are on the basis of lanthanide ions with thermally coupled energy levels, such as Er 3+ ( 2 H 11/2 and 4 S 3/2 ), 14−18 Ho 3+ ( 5 F 4 and 5 S 2 ), 19,20 Tm 3+ ( 3 F 2,3 and 3 H 4 ), 21−24 and Nd 3+ ( 4 F 5/2 and 4 F 3/2 ). 25−28 In these systems, there is a population inversion from the lower-lying level to the higher-lying level with lifting the temperature, consequently resulting in a change of the emission intensity ratio.…”
mentioning
confidence: 99%
“…Lanthanide-doped upconversion nanoparticles (UCNPs) possess abundant discrete energy levels with diverse thermal-dependent electronic transitions, which have attracted tremendous attention in the temperature sensor during the past decade. ,, Typically, the UCNPs based temperature thermometry are on the basis of lanthanide ions with thermally coupled energy levels, such as Er 3+ ( 2 H 11/2 and 4 S 3/2 ), Ho 3+ ( 5 F 4 and 5 S 2 ), , Tm 3+ ( 3 F 2,3 and 3 H 4 ), and Nd 3+ ( 4 F 5/2 and 4 F 3/2 ). In these systems, there is a population inversion from the lower-lying level to the higher-lying level with lifting the temperature, consequently resulting in a change of the emission intensity ratio. However, it should be noted that these systems usually show low temperature sensitivity (e.g., below 2% K –1 ) , because of the narrow energy gap between the thermally coupled energy levels required by Boltzmann distribution theory. In contrast, the design of thermometry with dual emitters based on nonthermally coupled emissions would present a chance to improve the sensitivity, which is able to result in a much larger LIR by manipulating their thermo-luminescent properties. , An ideal attempt is to design a system with contrary changes for the emission bands from the dual-emitter in the upconversion system, such as one emission increases while the other one decreases with temperature. , More importantly, the thermal enhancement of upconversion in some UCNPs was recently obtained by means of surface phonon-assisted energy transfer, lattice thermal expansion, negative thermal expansion of the lattice, , and moisture release. These progresses allow us to design the integrated upconversion nanosystems insisting of two species of upconversion emitters with different luminescence behaviors in the thermal field. As a result, the transitions in the dual-emitter can be fully thermally decoupled, making it highly desirable to realize the thermometry with much better sensitivity and flexibility.…”
mentioning
confidence: 99%